2011
DOI: 10.1016/j.amjmed.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Non-HDL Cholesterol Goal Attainment by Providers

Abstract: Purpose Despite improvements in low-density lipoprotein cholesterol goal attainment, non–high-density lipoprotein cholesterol (non-HDL-C) goal attainment remains poor. This study assessed providers’ knowledge of, attitude toward, and practice regarding non-HDL-C. Methods Based on a conceptual model, we designed a questionnaire which was administered to internal medicine, family practice, cardiology, and endocrinology providers attending continuous medical education conferences. Responses were compared to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…15,17,18 Knowledge gaps assessed include providers’ familiarity with the 2013 guideline; 10 year ASCVD risk estimator and its difference from the Framingham coronary heart disease (CHD) risk estimator as recommended by the prior ATP-III guideline document; intensity of statin therapy; 4 groups that could benefit from statin therapy (patients with clinical ASCVD; patients with diabetes aged 40–75 years and without clinical ASCVD; patients aged 40–75 years without clinical ASCVD or diabetes and with 10-year ASCVD risk ≥7.5%; and patients with possible familial hypercholesterolemia [FH, i.e., with LDL-C ≥190 mg/dL]). Gaps in attitude included assessment of providers’ agreement with the guideline and 10-year ASCVD risk estimator and the providers’ belief that he/she can perform guideline-recommended care.…”
Section: Methodsmentioning
confidence: 99%
“…15,17,18 Knowledge gaps assessed include providers’ familiarity with the 2013 guideline; 10 year ASCVD risk estimator and its difference from the Framingham coronary heart disease (CHD) risk estimator as recommended by the prior ATP-III guideline document; intensity of statin therapy; 4 groups that could benefit from statin therapy (patients with clinical ASCVD; patients with diabetes aged 40–75 years and without clinical ASCVD; patients aged 40–75 years without clinical ASCVD or diabetes and with 10-year ASCVD risk ≥7.5%; and patients with possible familial hypercholesterolemia [FH, i.e., with LDL-C ≥190 mg/dL]). Gaps in attitude included assessment of providers’ agreement with the guideline and 10-year ASCVD risk estimator and the providers’ belief that he/she can perform guideline-recommended care.…”
Section: Methodsmentioning
confidence: 99%
“…In the secondary prevention of CHD, physicians having knowledge of guidelines were more likely to initiate lipid-lowering treatment and to comply with an overall measure of guideline adherence 10. Another study also showed that a physician's lack of familiarity with and knowledge of guidelines were identified as important barriers to an appropriate management of dyslipidemia 11. Regarding the management of blood pressure, physicians familiar with the Joint National Committee guidelines were more likely to recognize the blood pressure threshold for initiating blood-pressure-lowering therapy as recommended in the guidelines 12.…”
Section: Discussionmentioning
confidence: 99%
“…(Oldridge, et al, 1999) Research has demonstrated the importance of helping patients identify specific behaviour as well as prioritizing goals in order to modify their risk factors and improve cardiac outcomes. (Ertzgaard, Ward, Wissel, & Borg, 2011;Virani et al, 2011) In contemporary health care, resource allocation is generally based on effectiveness in providing patient care, and cardiac rehabilitation is no exception. (Sanderson, Southard, & Oldridge, 2004) It is well know that cardiac rehabilitation coordinators provide high quality service, (Sanderson, et al, 2004) however without documented outcomes the evidence to support resource allocation is limited.…”
Section: Discussionmentioning
confidence: 99%